2021
DOI: 10.3389/fgene.2021.687687
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Disorder Genomics Data Analysis Elucidates a Shared Genetic Basis Between Major Depression and Osteoarthritis Pain

Abstract: Osteoarthritis (OA) and major depression (MD) are two debilitating disorders that frequently co-occur and affect millions of the elderly each year. Despite the greater symptom severity, poorer clinical outcomes, and increased mortality of the comorbid conditions, we have a limited understanding of their etiologic relationships. In this study, we conducted the first cross-disorder investigations of OA and MD, using genome-wide association data representing over 247K cases and 475K controls. Along with significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 97 publications
(113 reference statements)
3
10
0
Order By: Relevance
“…Conversely, chronic facial pain increased the risk of seeking care for depression (i.e., pain → depression only [Supplementary Table S7]). These findings are broadly consistent with other genetic studies concerning depression and chronic pain, which have shown genetic causal relationships between chronic pain and depression, spanning both depression → pain pathways [54][55][56][57][58] and pain → depression pathways. 20,52,55,59 Taken together, our results and previous findings 19,20,27,54,55 raise further intriguing hypotheses, such as that either or both causal directions may exist on a patient sub-group basis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Conversely, chronic facial pain increased the risk of seeking care for depression (i.e., pain → depression only [Supplementary Table S7]). These findings are broadly consistent with other genetic studies concerning depression and chronic pain, which have shown genetic causal relationships between chronic pain and depression, spanning both depression → pain pathways [54][55][56][57][58] and pain → depression pathways. 20,52,55,59 Taken together, our results and previous findings 19,20,27,54,55 raise further intriguing hypotheses, such as that either or both causal directions may exist on a patient sub-group basis.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are broadly consistent with other genetic studies concerning depression and chronic pain, which have shown genetic causal relationships between chronic pain and depression, spanning both depression → pain pathways [54][55][56][57][58] and pain → depression pathways. 20,52,55,59 Taken together, our results and previous findings 19,20,27,54,55 raise further intriguing hypotheses, such as that either or both causal directions may exist on a patient sub-group basis. 52 Our LCV results also implicate a history of trauma or stressincluding death of a close relative in last two years; being adopted as a child; sexual assault; marital separation; and military serviceas genetic causal factors for various chronic pain types.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recently, Barowsky et al used cross-disorder genome-wide genetic data analysis to examine the etiological relationship between OA and MDD. 67 After a series of pleiotropic analyses, the findings suggest that OA and MDD share common genetic risk mechanisms, one of which centers on the neural response to the sensation of mechanical stimulus. 67 This suggests that the two diseases may share a common genetic risk mechanism.…”
Section: Potential Mechanisms Of Oa and Comorbid Depressionmentioning
confidence: 99%
“… 67 After a series of pleiotropic analyses, the findings suggest that OA and MDD share common genetic risk mechanisms, one of which centers on the neural response to the sensation of mechanical stimulus. 67 This suggests that the two diseases may share a common genetic risk mechanism. In addition, Boer et al conducted a genome-wide association study meta-analysis across 826,690 individuals (177,517 with OA) and found that OA shares genetic components with multiple traits, including depressive symptoms.…”
Section: Potential Mechanisms Of Oa and Comorbid Depressionmentioning
confidence: 99%